Lecture in Post-secondary Education Institution within the Context of Competence Approach - N. V. Shestak (Высшее образование в России)
This article addresses a problem of the potential of a university lecture. On the one hand, training of highly qualified personnel should meet the modern  requirements, and on the other hand, lecture remains the main form of  holding a tutoring at university. An analysis of attributes of higher education  modern pedagogical system, such as a purpose of system functioning,  subjects (students, teachers, etc.), content of training, made it possible to  conclude about qualitative changes in their nature, characteristics,  requirements related to the new realities of modern society. The old  stereotypes and attitudes which have been being formed for centuries and  have already lost their value, but continue to dictate forms, means and  methods of educational process organization are a hindrance to the  development of higher education. The need of society and state for qualified personnel has led to introduction of competence-based approach in  training of specialists who have an activity orientation, an ability to fulfill  functional duties, to solve professional problems. Development of  professional competences is possible only in the conditions of the  implementation of practice-based educational/professional activity, specially  organized students’ self-reliant work, immediate application of knowledge  acquired for the solution of various tasks.